Analisis Tingkat Kepuasan Konsumen Pada Restoran Menggunakan Logika Fuzzy Tsukamoto - Harahap, Inun Suryani; Santoso, Heri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Tsukamoto fuzzy logic method is used to measure the level of customer satisfaction at Mixue Restaurant. The background of this study is the importance of understanding and improving customer satisfaction in the highly competitive restaurant industry. Mixue attracts the attention of many people, especially students, as one of the restaurants that offers contemporary drinks at affordable prices. Mixue Jamin Ginting, Medan, questionnaires were distributed to 100 people to conduct this study. The variables analyzed were service quality, location, price, and facilities. By using the Fuzzy Tsukamoto method, consumer satisfaction values ​​in fuzzy sets such as